Pupae of Mesozoic Jurochlus Kalugina, 1985 (Diptera: Chironomidae), with description of four new species - Lukashevich, Elena D.; Przhiboro, Andrey A. (Zootaxa, 2012)
The Mesozoic chironomid genus Jurochlus Kalugina, 1985, known only as pupae, is reviewed. Four new species ofJurochlus are described from the Upper Jurassic and Lower Cretaceous deposits of Mongolia, viz. J. trivittatus sp. nov.,J. limbatus sp. nov., J. lineatus sp. nov. (Shar Teg, J 3 ) and J. adustus sp. nov. (Khutel Khara, J 3 /K 1 ). Both previouslydescribed species, J. sibiricus Kalugina, 1985 and J. rigor Kalugina, 1985, are re-described in detail based on re-examination of the holotypes. The diagnosis of the genus Jurochlus is emended and its systematic position (probably Podonominae or Tanypodinae) is discussed.